2019
DOI: 10.1152/ajpregu.00221.2018
|View full text |Cite
|
Sign up to set email alerts
|

Protein recycling and limb muscle recovery after critical illness in slow- and fast-twitch limb muscle

Abstract: An impaired capacity of muscle to regenerate after critical illness results in long-term functional disability. We previously described in a long-term rat peritonitis model that gastrocnemius displays near-normal histology whereas soleus demonstrates a necrotizing phenotype. We thus investigated the link between the necrotizing phenotype of critical illness myopathy and proteasome activity in these two limb muscles. We studied male Wistar rats that underwent an intraperitoneal injection of the fungal cell wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Oxidative muscles seem to be highly susceptible to abnormalities induced by sepsis. Preau et al have identified a necrotizing phenotype in SOL muscle of rats exposed to a model of peritonitis in contrast to the glycolytic gastrocnemius muscle, which did not display the necrotic phenotype (Preau et al, 2019). Owen et al (2019) demonstrated that sepsis, induced via cecal slurry injection, caused EDL weakness, but not atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative muscles seem to be highly susceptible to abnormalities induced by sepsis. Preau et al have identified a necrotizing phenotype in SOL muscle of rats exposed to a model of peritonitis in contrast to the glycolytic gastrocnemius muscle, which did not display the necrotic phenotype (Preau et al, 2019). Owen et al (2019) demonstrated that sepsis, induced via cecal slurry injection, caused EDL weakness, but not atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to expect that accumulation of macrophages and other inflammatory cell populations would result in higher production of ROS. High ROS production is associated with halted protein synthesis and accelerated protein degradation due to enhanced proteasome proteolytic degradation and autophagy pathways (Callahan & Supinski, 2009; Powers et al, 2012; Preau et al, 2019; Wollersheim et al, 2014). Whether and when these pathways are upregulated over the course of the myopathy, in our double‐hit model, warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Critically ill patients face multiple risk factors causing myopathies such as immobilization, local inflammation‐induced by systemic mediators, and nutritional defects (Friedrich et al , ). Mechanisms responsible for septic myopathy include sodium channel dysfunction with upregulation of non‐selective channels (Balboa et al , ), ubiquitin–proteasome pathway protein proteolysis, proteasome activation and increased autophagy (Wollersheim et al , ; Preau et al , ), changes in intracellular calcium levels leading to excitation‐contraction uncoupling (Batt et al , ), and mitochondrial derangements with an increase in free radical generation (Zolfaghari et al , ). Although autophagy is among the mechanisms of protein loss, its balanced activation can protect muscles from the accumulation of toxic proteins (Morel et al , ).…”
Section: Sepsis: a New Who Global Health Prioritymentioning
confidence: 99%
“…Autophagy as part of the programmed death pathways is linked to oxidative stress [5,16,54,73,[135][136][137][138][139][140]. Autophagy induction recycles cytoplasmic organelles and components for tissue remodeling [14,141] and can remove non-functional organelles [8, 73,136,142]. Macroautophagy recycles organelles in cells and sequesters cytoplasmic proteins into autophagosomes.…”
Section: Circadian Clock Genes and Pathways Of Autophagymentioning
confidence: 99%